2011
DOI: 10.5713/ajas.2011.11196
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Pulmonary Artery Copper Concentrations and Genes Involved in Copper Homeostasis in Cattle, Swine, and Goats

Abstract: Liver and pulmonary artery tissue from 5 Angus cross bred steers, 6 goats, and 6 pigs were collected at a commercial abattoir to examine the relationship of pulmonary artery copper (Cu) concentrations and genes involved in copper homeostasis. Liver and pulmonary artery samples were collected at the time of harvest and snap frozen. Liver and pulmonary artery Cu concentrations were determined via flame atomic absorption spectrophotometry and gene expression was determined via real time PCR. Liver Cu concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…There is a shortage of data in ruminants regarding the effect of CuD on cardiac Cu regulation genes. Nevertheless, our results were consistent with previously reported data in other species (Dermauw et al 2014, Getz et al 2011, Han et al 2009, Han et al 2012, Hepburn et al 2009. Simmental cattle, a highly susceptible breed to CuD, showed reduced mRNA expression of COX17, CTr1, and ATP7A in duodenal tissue, placenta, and liver compared with the non-de cient breed (Fry 2011, Fry et al 2013.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is a shortage of data in ruminants regarding the effect of CuD on cardiac Cu regulation genes. Nevertheless, our results were consistent with previously reported data in other species (Dermauw et al 2014, Getz et al 2011, Han et al 2009, Han et al 2012, Hepburn et al 2009. Simmental cattle, a highly susceptible breed to CuD, showed reduced mRNA expression of COX17, CTr1, and ATP7A in duodenal tissue, placenta, and liver compared with the non-de cient breed (Fry 2011, Fry et al 2013.…”
Section: Discussionsupporting
confidence: 93%
“…The correlation between Cu concentration and the investigated genes in the cardiac tissues revealed no signi cant correlation. A variable correlation between pulmonary artery Cu concentration and mRNA expression of Cu regulating genes was also observed in goats, cattle, and pigs (Dermauw et al 2014, Han et al 2012 in which the authors suggested that these genes are regulated differently among species.…”
Section: Discussionmentioning
confidence: 91%
“…The LOXL1 is fundamental for the crosslinking between collagen and elastin, ensuring the elasticity of the extracellular matrix in organs where the gene is expressed [ 122 , 123 ]. The influence of LOXL1 was described on copper concentrations in the liver and pulmonary artery of swine through the establishment of elastic fibers, which may be related to the adipogenesis of subcutaneous preadipocytes linked to ontogenetic pathways [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mineral homoeostasis is controlled mainly by absorption mechanisms (Field 1981) and may help explain these differences. However, current understanding of the mechanisms for mineral absorption in beef cattle are limited (Spears 2003; Han et al 2012).…”
Section: Discussionmentioning
confidence: 99%